2016
DOI: 10.1371/journal.pone.0150807
|View full text |Cite
|
Sign up to set email alerts
|

The German Version of the Gaze Anxiety Rating Scale (GARS): Reliability and Validity

Abstract: ObjectiveFear of eye gaze and avoidance of eye contact are core features of social anxiety disorders (SAD). To measure self-reported fear and avoidance of eye gaze, the Gaze Anxiety Rating Scale (GARS) has been developed and validated in recent years in its English version. The main objectives of the present study were to psychometrically evaluate the German translation of the GARS concerning its reliability, factorial structure, and validity.MethodsThree samples of participants were enrolled in the study. (1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…Empirical evidence demonstrating that socially anxious individuals actually exhibit gaze avoidance is far more equivocal than expected 7 9 . On the one hand, and in line with clinical observations 21 , 22 and SAD patients’ self-reports 23 , research has shown that individuals with sub-clinically and clinically relevant social anxiety levels display gaze patterns consistent with avoiding gaze 6 , 24 . On the other hand, however, there is also evidence of normal or increased eye gaze in socially anxious individuals 25 .…”
Section: Introductionmentioning
confidence: 55%
See 1 more Smart Citation
“…Empirical evidence demonstrating that socially anxious individuals actually exhibit gaze avoidance is far more equivocal than expected 7 9 . On the one hand, and in line with clinical observations 21 , 22 and SAD patients’ self-reports 23 , research has shown that individuals with sub-clinically and clinically relevant social anxiety levels display gaze patterns consistent with avoiding gaze 6 , 24 . On the other hand, however, there is also evidence of normal or increased eye gaze in socially anxious individuals 25 .…”
Section: Introductionmentioning
confidence: 55%
“…With these considerations in mind, we set out to study whether self-reported gaze anxiety is associated with gaze behavior in naturalistic, face-to-face social interactions. For that purpose, we a priori created groups of participants reporting either high or low levels of gaze anxiety using the Gaze Anxiety Rating Scale 20 , 23 . To generate comparable experimental conditions across participating groups, participants then performed a semi-structured interaction (“fast-friends procedure” 42 ) with a previously unknown individual reporting a medium level of gaze anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…A further limitation in our study is the scale we used to measure social anxiety traits. Although the GARS positively correlates with other measures associated with Social Anxiety (i.e., the Leibowitz Social Anxiety Scale), it is not a measure of social anxiety and is in fact a different construct of anxiety-driven gaze avoidance (Domes, Marx, Spenthof, & Heinrichs, 2016; Liebowitz, 1987). As such, although we found gaze aversion differences in participants who scored highly in GARS scores, this is not very surprising as it is exactly what that scale is supposed to measure.…”
Section: Limitations and Future Directionsmentioning
confidence: 94%
“…These are widely used self-report scales that evaluate two different categories of feared situations in social anxiety disorders: those related to being observed by others (SPS), and those related to social interaction (SIAS). Finally, the German version of the Gaze Anxiety Rating Scale (GARS) was used to measure self-reported fear and avoidance of making eye contact in social situations 34 .…”
Section: Methodsmentioning
confidence: 99%